Cameroon : Requests for Disbursement Under the Rapid Credit Facility, Extension of the Extended Credit Facility Arrangement, and Rephasing of Access-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Cameroon. (International Monetary Fund, 2021)
This paper focuses on Cameroon's Requests for Disbursement Under the Rapid Credit Facility (RCF), Extension of the Extended Credit Facility (ECF) Arrangement, and Rephasing of Access. The outbreak of the coronavirus disease 2019 pandemic and the terms of trade shocks from the sharp fall in oil prices are having a significant impact on Cameroon's economy, leading to a historic fall of real gross domestic product growth. The authorities are taking decisive actions to limit the spread of the virus and its economic and social impact. They have implemented strong crisis containment and mitigation measures and are scaling up spending to bolster their health response. Additional measures currently under consideration will provide support to vulnerable households and firms. IMF emergency financing under the RCF will support the government's efforts to mitigate the impact of the twin shocks. Additional assistance from development partners will be critical to fill the remaining financing need. Strict budgetary controls and transparency will be needed to ensure that the assistance under the RCF meets its intended objectives.